RESEARCH ON THE INFLUENCE OF A SWITCHED-MODE POWER SUPPLY ON THE TRANSMISSION PARAMETERS OF A HOUSE ELECTRICAL WIRING NETWORK - YANEVYCH, OLEKSANDR; TRYFONOVA, KSENIIA; KOVALOV, OLEKSII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The rapid growth in the number of smart devices equipped with wireless interfaces, and consequently, the emergence of mutual interference between them, drives the search for alternative interfaces that could be used in the deployment of smart home and smart city concepts. Most smart devices are equipped with a port for connection to an AC power network. In this context, a good decision is the use of PLC technology, which enables broadband access via household electrical wiring networks (HEWNs).The design of access networks using PLC technology requires an understanding of how different types of loads affect the parameters of the signal propagation medium – HEWNs. This article is dedicated to studying the impact of switched-mode power supplies (SMPS) of various power ratings on the transmission parameters of HEWNs. The influence of SMPS components is analyzed, with particular attention to the effect of the SMPS input filter on HEWN transmission parameters in the context of an HEWN fragment with a single branch, formed by wire segments of type SHVVP with a copper conductor cross-sectional area of 1.5 mm².Using the method for determining transmission parameters, which considers the HEWN as a cascaded connection of two-port networks, calculations were performed for the insertion loss and phase of the propagation constant of the HEWN. The obtained results were analyzed and compared with the characteristics for the case of a matched load (wave impedance), as well as for open-circuit and short-circuit load conditions. The influence of SMPS power variation on the frequency characteristics of insertion loss and the phase of the propagation constant of the HEWN was also examined. The study was conducted for the frequency range from 0 to 30 MHz, corresponding to the 25 MHz – PB frequency band according to ITU-T Recommendation G.9964.
Keywords: power line communication; broadband access; transmission parameters; switched-mode power supply